Performance investigation of 3z buck boost converter for renewable applications - Kishor, G; Harsha Vardhan Reddy, M; Pushpalatha, K (International Journal of Engineering and Technology, 2018)
In case of renewable generation systems like Solar, Wind and Fuel cell it is required to use DC-DC converter to increase the voltage levels to meet demand. In such case the operating efficiency of dc-dc converter plays a vital role in energy conversion generally lie in the range of 60-80 percent. In this paper a 3-Z cascaded network is proposed for the renewable energy applications operating at higher efficiency. A comparison is made between conventional dc-dc buck boost converter with the proposed 3-Z cascaded network and analyzed its performance with lighting load. Simulation analysis is also performed to validate the proposed converter behavior.Â Â